2014
DOI: 10.3347/kjp.2014.52.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Effects of Helianthemum lippii (L.) on Acanthamoeba castellanii Cysts in Vitro

Abstract: Acanthamoeba spp. commonly cause Acanthamoeba keratitis which is typically associated with the wear of contact lenses. Therefore, finding an economic, efficient, and safe therapy of natural origin is of outmost importance. This study examined the in vitro lethal potential of ethyl acetate and methanol extracts of Helianthemum lippii (L.) (sun roses) against Acanthamoeba castellanii cysts isolated from patients with amoebic keratitis. Both extracts proved to be potent as regard to their lethal effects on A. cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Trophozoites feed on bacteria, algae or yeast or grow axenically on nutrients [ 1 ]. Encystment occurs when conditions become unfavorable, such as during lack of nutrients or desiccation and cysts are highly resistant to temperature and pH changes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trophozoites feed on bacteria, algae or yeast or grow axenically on nutrients [ 1 ]. Encystment occurs when conditions become unfavorable, such as during lack of nutrients or desiccation and cysts are highly resistant to temperature and pH changes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the tested plants (Arachis hypogaea, Curcuma longa, Pancratium maritimum) showed higher growth inhibitory percentages up to 100% by their maximum effective tested doses. In another in vitro study, ethyl acetate and methanol extract of Helianthemum lippii showed higher lethal effect against Acanthamoeba castellanii cysts than chlorhexidine (Badria et al 2014). Also, Ismail et al (2018) stated that different concentrations of both aqueous and alcoholic extracts of Nigella sativa possessed more potent cysticidal effect on Acanthamoeba cysts with growth inhibition up to 100% compared to chlorhexidine 0.02% which gave growth inhibitory effect ranging from 56 to 80% throughout the experiment.…”
Section: Discussionmentioning
confidence: 97%
“…In the same year, Shoaib et al [47] reported the activities of methanolic plant extracts on the viability of Acanthamoeba castellanii (T4 genotype) and its cytotoxic efficacy on human corneal epithelial cells. The plant crude extracts (maximum dose, 1.5 mg/ml) inhibited and killed > 50% of trophozoites within 1 h. In vitro amoebicidial activity of Helianthemum lippii (L.) methanol and ethyl acetate extracts on Acanthamoeba castellanii cysts was represented by Badria et al [3]. Although both extracts demonstrated potent lethal activity on A. castellanii cysts, the ethyl acetate extract was more effective than the methanol extract.…”
Section: Discussionmentioning
confidence: 97%